Faglige oplysninger i monolingvale betydningsordbøger - Bergenholtz, Henning (LexicoNordica, 1994)
Monolingual defining dictionaries often give the impression of explaining socially relevant terms from a wide range of different subject fields. In practice, they include but a fraction of the millions of terms in the various subject fields, of course. At the same time, however, this particular part of the lemma stock of general-language dictionaries presents a number of special problems - both to the lexicographer and the user. Even a major lexicographical staff will not have the necessary encyclopedic knowledge and the involvement of a number of experts requires extensive and labour-intensive collaboration. Besides, this would significantly increase the cost of the entire project. If a general-language dictionary provided very precise encyclopedic information, however, this information would be difficult to understand for the intended users. On the other hand, no user would benefit from so rudimentary explanations that the expert would consider them imprecise. There is no universal solution to this dilemma, which is closely connected with the theoretical problems that so far remain unsolved.